2016
DOI: 10.18632/oncotarget.13889
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma RNA profiling uncovers a distinct non-coding RNA signature

Abstract: Ameloblastoma of the jaws remains the top difficult to treat odontogenic tumour and has a high recurrence rate. New evidence suggests that non-coding RNAs (ncRNAs) play a critical role in tumourgenesis and prognosis of cancer. However, ameloblastoma ncRNA expression data is lacking. Here we present the first report of ameloblastoma ncRNA signatures. A total of 95 ameloblastoma cases and a global array transcriptome technology covering > 285.000 full-length transcripts were used in this two-step analysis. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…This study focused exclusively on candidate genes known to be mutated in AM, [11][12][13][14] and it is possible that other oncogenic or tumour suppressor genes could be mutated in CAA, including noncoding RNAs. 31 Furthermore, these data do not ascertain whether the HRAS p.Q61R mutation acts as a primary or secondary oncogenic driver in CAA. Therefore, additional studies are required, especially considering that the biological effects of RAS mutations (ie, proliferation vs senescence) depend on the level of expression of the mutated allele, among other variables.…”
Section: Polya+mentioning
confidence: 96%
See 1 more Smart Citation
“…This study focused exclusively on candidate genes known to be mutated in AM, [11][12][13][14] and it is possible that other oncogenic or tumour suppressor genes could be mutated in CAA, including noncoding RNAs. 31 Furthermore, these data do not ascertain whether the HRAS p.Q61R mutation acts as a primary or secondary oncogenic driver in CAA. Therefore, additional studies are required, especially considering that the biological effects of RAS mutations (ie, proliferation vs senescence) depend on the level of expression of the mutated allele, among other variables.…”
Section: Polya+mentioning
confidence: 96%
“…This study focused exclusively on candidate genes known to be mutated in AM, and it is possible that other oncogenic or tumour suppressor genes could be mutated in CAA, including non‐coding RNAs . Furthermore, these data do not ascertain whether the HRAS p.Q61R mutation acts as a primary or secondary oncogenic driver in CAA.…”
Section: Clinical Information and Hras Mutation Status Of Dogs Includmentioning
confidence: 99%
“…Therefore, it is quite reasonable to speculate that as the regulator of TRIM25, the expression pattern of SNORD17 may also be sensitive to distinguish the different cancer subtypes. Interestingly, Davanian et al [30] rst identi ed SNORA11 as a distinct ncRNA signature of ameloblastoma. Herein, our methylation correlation analysis showed that SNORD17 and SNORA11 were also negatively correlated with methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the expression level of snoRNAs have also been associated with cancer. Dysregulation of snoRNA expression has been reported in different types of cancers, from leukemia [26] to carcinoma [27] and even sarcoma [28]. Due to these alterations in snoRNA expression, these small RNAs have been considered as potential biomarkers in cancer for several years.…”
Section: Clinical Significance Of Snornas In Human Diseasesmentioning
confidence: 99%